A multi-proxy study of Holocene environmental change in the Maya lowlands of Peten, Guatemala - Curtis, J. H.; Brenner, M.; Hodell, D. A.; Balser, R. A.; Islebe, G. A.; Hooghiemstra, H. (Journal of Paleolimnology, 1998)
We used multiple variables in a sediment core from Lake Peten-Itza, Peten, Guatemala, to infer Holocene climate change and human influence on the regional environment. Multiple proxies including pollen, stable isotope geochemistry, elemental composition, and magnetic susceptibility in samples from the same core allow differentiation of natural versus anthropogenic environmental changes. Core chronology is based on AMS (14)C measurement of terrestrial wood and charcoal and thus avoids the vagaries of hard-water-lake error. During the earliest Holocene, prior to similar to 9000 (14)C yr BP, the coring site was not covered by water and all proxies suggest that climatic conditions were relatively dry. Water covered the coring site by similar to 9000 (14)C yr BP, coinciding with filling of other lakes in Peten and farther north on the Yucatan Peninsula. During the early Holocene (similar to 9000 to similar to 6800 (14)C yr BP), pollen data suggest moist conditions, but high delta(18)O values are indicative of relatively high E/P. This apparent discrepancy may be due to a greater fractional loss of the lake's water budget to evaporation during the early stages of lake filling. Nonetheless, conditions were moist enough to support semi-deciduous lowland forest. Decrease in delta(18)O values and associated change in ostracod species at similar to 6800 (14)C yr BP suggest a transition to even moister conditions. Decline in lowland forest taxa beginning similar to 5780 (14)C yr BP may indicate early human disturbance. By similar to 2800 (14)C yr BP, Maya impact on the environment is documented by accelerated forest clearance and associated soil erosion. Multiple proxies indicate forest recovery and soil stabilization beginning similar to 1100 to 1000 (14)C yr BP, following the collapse of Classic Maya civilization.
Zj856Times Cited:92Cited References Count:96

A Holocene vegetation history from lowland Guatemala - Islebe, G. A.; Hooghiemstra, H.; Brenner, M.; Curtis, J. H.; Hodell, D. A. (Holocene, 1996)
A 5.45-m core from Lake Peten-Irza, lowland Guatemala, contains a near-complete record of Holocene sedimentation. The age-depth relationship for the core is based on AMS C-14 dating of terrestrial wood fragments and provides a reliable chronology in this karst region where hard-water lake error has typically confounded sediment geochronology. In the basal part of the sequence, pollen of the Moraceae-Urticaceae group dominate, indicating the presence of widespread tropical forest during the early Holocene (c. 8600-5600 yr BP). Relative abundance of pollen of high forest taxa declined beginning as early as 5600 yr BP, indicating climatic drying or perhaps initial land clearance. Deforestation by prehistoric Mayan inhabitants is documented clearly in the pollen record beginning about 2000 pr BP (106 cal BC-122 cal Ao, 95.4%, 2 sigmas) by the appearance of disturbance taxa (e.g. Ambrosia and Poaceae) and presence of Zea. Forest regrowth occurred following the Classic Maya collapse, c. AD 900, as reflected by a relative increase in Moraceae-Urticaceae pollen.
Vh189Times Cited:103Cited References Count:44